2000
DOI: 10.1097/00001756-200008210-00037
|View full text |Cite
|
Sign up to set email alerts
|

Decreased inhibition by leptin of hypothalamic arcuate neurons in neonatally overfed young rats

Abstract: Rats neonatally overnourished due to a reduced litter size develop persisting overweight throughout life. A presumed mechanism leading to this 'malprogramming' consists of an acquired change of the responsiveness to leptin of the neuronal system regulating feeding behavior. The study reports significant differences in the effects of leptin on single unit activity of the arcuate nucleus in brain slices of normal compared with early postnatally overfed juvenile rats. The firing rate of arcuate neurons in normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 6 publications
5
64
0
3
Order By: Relevance
“…The hyperleptinaemia exhibited by the obese SL rats suggested that a state of leptin resistance might exist at the hypothalamic level [15][16][17][18], explaining the hyperphagia observed in this model [22,45,49]. In order to study this issue further, mRNA levels encoding the different leptin receptor isoforms were determined in the hypothalamus of NL, SL and LL rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperleptinaemia exhibited by the obese SL rats suggested that a state of leptin resistance might exist at the hypothalamic level [15][16][17][18], explaining the hyperphagia observed in this model [22,45,49]. In order to study this issue further, mRNA levels encoding the different leptin receptor isoforms were determined in the hypothalamus of NL, SL and LL rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest the existence of alterations in the hypothalamic feeding-regulation systems in the postnatal overfeeding model. It has already been shown that these rats are hyperleptinaemic with central leptin resistance [15][16][17][18] and hyperinsulinaemic with central insulin resistance [19,20]. However, there are no data about the mechanisms underlying this programmed leptin resistance and the possible changes induced by early nutrition on the expression of hypothalamic neuropeptides.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of overnutrition on hypothalamus function has been observed both in sheep in which the neural network is relatively mature at birth as in humans 69 and in rodents in which the circuits are not fully mature until postnatal day 16. 70 For example, overfeeding rat pups by rearing them in small litters leads to an increased food intake in the perinatal period and this was also associated with a persistent increase in appetite drive in later life. [64][65][66]70 In rodents, exposure to a diabetic environment before birth or exposure in early postnatal life results in significant changes in the architecture of the hypothalamus including a decrease in neuronal density within the ventromedial hypothalamic nucleus, which is associated with the inhibition of food intake and pancreatic insulin secretion, and an increase in neuronal density within the dorsomedial hypothalamic nucleus, which is involved in promoting body weight gain and food intake.…”
Section: The Developmental Origins Of Human Metabolic Diseasementioning
confidence: 99%
“…70 For example, overfeeding rat pups by rearing them in small litters leads to an increased food intake in the perinatal period and this was also associated with a persistent increase in appetite drive in later life. [64][65][66]70 In rodents, exposure to a diabetic environment before birth or exposure in early postnatal life results in significant changes in the architecture of the hypothalamus including a decrease in neuronal density within the ventromedial hypothalamic nucleus, which is associated with the inhibition of food intake and pancreatic insulin secretion, and an increase in neuronal density within the dorsomedial hypothalamic nucleus, which is involved in promoting body weight gain and food intake. 71 In adult offspring of gestational diabetic rats, there was also an increase in neuropeptide Y and galanin neurons in the arcuate hypothalamic nucleus, suggesting that gestational maternal diabetes promotes the malformation of the hypothalamic neurons and the dysregulation of the appetite-controlling regulatory network, resulting in obesity and metabolic disturbances in later life.…”
Section: The Developmental Origins Of Human Metabolic Diseasementioning
confidence: 99%
“…Ce pic de leptine est accru lors d'une surnutrition maternelle [9] et fortement diminué lors de la malnutrition maternelle. Cette diminution des concentrations plasmatiques chez le nouveau-né entraîne une réduction de la densité des projections axonales hypothalamiques [11,12]. De même, les taux périnatals d'insuline influencent positivement l'architecture de l'hypothalamus en augmentant le nombre de neurones et l'élongation des prolongements axonaux [13,14].…”
unclassified